Through Circularity Towards Sustainability: Assessing the Progress and Challenges of the Circular Economy in the EU and Slovakia - Huttmanová, Emília; Chovancová, Jana; Steiner, Martin J.F.; Ramharter, Peter M.; Kočiščáková, Kristína (European Journal of Sustainable Development, 2023)
Sustainable development poses a significant challenge to modern civilization. The current problems and crises underscore the urgent need to establish a sustainable society, marking a crucial milestone in human evolution. The concept of sustainability has gained increasing prominence as a scientific, social, and political concern. The European Union strongly emphasizes the transition to a circular economy as a sustainable approach to economic growth. This circular economy model, one of the transformative policies of the Green Deal, is intended to pave the way for a sustainable future. It is now recognized as one of several approaches to achieving sustainability, as it encompasses and interconnects the economic, social, and environmental aspects of sustainable development. The main objective of this paper is to assess the present state and progress of the circular economy in Slovakia, employing selected indicators within the context of transitioning from a linear to a circular economy. Keywords: Circular economy. Sustainability. Municipal waste. Recycling rate. European Union countries.